2015
DOI: 10.1098/rsob.150138
|View full text |Cite
|
Sign up to set email alerts
|

The miR-302/367 cluster: a comprehensive update on its evolution and functions

Abstract: microRNAs are a subclass of small non-coding RNAs that fine-tune the regulation of gene expression at the post-transcriptional level. The miR-302/367 cluster, generally consisting of five members, miR-367, miR-302d, miR-302a, miR-302c and miR-302b, is ubiquitously distributed in vertebrates and occupies an intragenic cluster located in the gene La-related protein 7 (LARP7). The cluster was demonstrated to play an important role in diverse biological processes, such as the pluripotency of human embryonic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 72 publications
0
61
0
1
Order By: Relevance
“…miR-302-3p is a member of the miR-302-3p-367 cluster, which has been demonstrated to be specifically expressed in human embryonic stem cells (25). Additionally, the miR-302-3p-367 cluster has potential to convert somatic cells into induced pluripotent stem cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…miR-302-3p is a member of the miR-302-3p-367 cluster, which has been demonstrated to be specifically expressed in human embryonic stem cells (25). Additionally, the miR-302-3p-367 cluster has potential to convert somatic cells into induced pluripotent stem cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐367‐3p is a member of the miR‐302/367 gene cluster located within the 4q25 region of the human genome . miR‐367‐3p is involved in regulating a wide range of biological functions and participates in the disease progression of various cancers . Multiple forms of evidence have suggested that miR‐367‐3p expression is downregulated in various cancers, and the overexpression of miR‐367‐3p restricts tumour growth and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al () showed that miR‐106b/25 cluster inhibits ER stress‐induced cell death. miR‐302/367 cluster is involved with differentiation and self‐renewal and is also reported to regulate ER homeostasis (Gao, Zhu & Dou, ). Taken together, miRNA clusters are involved in cross talk with the ER in maintaining the normal homeostasis of the cell.…”
Section: Significance Of Mirna Clusters In Health and Diseasementioning
confidence: 99%